A multiproxy palaeoecological record of Holocene lake sediments from the Rio Tapajos, eastern Amazonia - Irion, G.; Bush, M. B.; de Mello, J. A. N.; Stuben, D.; Neumann, T.; Muller, G.; De, J. O.; Junk, J. W. (Palaeogeography Palaeoclimatology Palaeoecology, 2006)
Two sediment cores up to 42 m in length were raised from the wide, deep, section of the lower Tapajos River, Amazonia, referred to as Lago Tapajos. These cores reveal a history of subtle environmental change that began with the formation of Lago Tapajos as sea level rose about 11,000 years ago. The sediments of the lake were deposited fairly quickly-at a rate of ca. 4 m per millennium and are uniformly fine grained, with low organic content. The fossil pollen record derived from these sediments reveals that forest surrounded this site throughout the Holocene. The largest change in the core took place between ca. 5500 and 4200 cal. years BP and reflects a transition from coarser to finer sediments. Coincident with the change in sediment is a slight transition in the pollen spectra with an increase in Poaceae abundance at the expense of the pioneer tree Cecropia cecropia. A tentative explanation is offered in which increased human activity, possibly spurred by climatic change, resulted in the formation of some local grasslands. However, despite the apparent actions of humans, there is no indication of basin-wide transformation of landscapes in this record. The Holocene persistence of forest as the dominant landscape matrix around Lago Tapajos is supported by low delta C-13 values and by the constant geochemistry and mineralogy of the lake sediments. (c) 2006 Elsevier B.V. All rights reserved.
097fbTimes Cited:40Cited References Count:78